PENGARUH BAURAN PEMASARAN JASA TERHADAP KEPUASAN WISATAWAN BERKUNJUNG KE TAMAN BUNGA SAPO JUMA TONGGING KARO - Girsang, Meyga Kristina; Sianipar, Gloria J.M; Simanjuntak, Agus Nakkok (Jurnal Manajemen dan Bisnis, 2022)
This study aims to determine the effect of the service marketing mix on tourist satisfaction at yhe Sapo Juma Flower Garden. Tongging Karo. The number of the samples of this study were 100 respondents. The results of the t test show that : (1) the product has a positive and significant effect on tourist satisfaction, (2) the price has a negative effect on tourist satisfaction, (3) the place has a positive but not significant effect on tourist satisfaction, (4) the promotion has a positive but not significant effect on tourist satisfaction, (5) the people has a positive but not significant effect on tourist satisfaction, (6) the process has a negative effect on tourist satisfaction, (7) the phisical evidence has a positive and significant effect on tourist satisfaction. The result of the F test shows that the marketing mix together has a positive and significant effect on tourist satisfaction. The result of the coefficient determination or R square shows that the variable product, price, place, promotion, people, process and physical evidence can explain tourist satisfaction of 0.784 or 78.4% while the remaining of 0.216 or 21.6% is explained by other variables not examined.